EFFECT OF SEASON ON FIRST LACTATION PRODUCTION PERFORMANCE OF MURRAH BUFFALOES - BARMAN, R.S.D.; GREWAL, S.S.; JHA, D.K. (Indian Journal of Animal Production and Management, 2017)
ABSTRACT The present investigation was conducted on 301 Murrah buffaloes maintained at Buffalo Research center, Department of Livestock Production and Management, CCS Haryana Agriculture University, Hisar (India) with the main objective to study the Effect of season on first lactation production performance of Murrah buffaloes. The overall least-squares means first lactation milk yield, first lactation length, first peak yield and first dry period were obtained as 1991.46 ± 26.37 kg, 381.67 ± 3.82 days, 9.58 ±0.99 kg and 188.39 ± 5.05 respectively. The period of calving had significant effect on first peak yield and first dry period. Season of calving had significant effect on first lactation milk yield, first dry period and first lactation length. Each year was divided in to four season i.e. Summer, Rainy, Autumn and Winter. The least squares means for FLMY indicated that summer (April to June) calvers produced highest milk (2152.17±57.74) yield followed by winter (December to March) calvers but there was no significant difference in summer and winter calvers. Key words : First lactation, Production, Buffaloes, Season